Effect of pressure fluctuations on control accuracy of hydroturbine parameters - Канюк, Геннадий Иванович; Мезеря, Андрей Юрьевич; Ириков, Дмитрий Валерьевич; Мельников, Вячеслав Евгеньевич (Eastern-European Journal of Enterprise Technologies, 2014)
Ensuring effective automatic control of hydraulic turbines is an important and relevant scientific and technical task, which will allow to improve technical and economic characteristics and reliability of hydraulic units, as well as the frequency stability of electricity, generated by hydraulic power plants. Pulsations of pressure and flow rate, as well as other disturbance parameters, which inevitably arise during its operation, should not significantly change the turbine characteristics and lead to a considerable increase in the load on the structural elements, but due to the presence of high-Q resonances in hydraulic turbines, the issues on reducing its automatic control system stability and its impact on the hydraulic unit operation as a whole remain open. The analysis of pressure oscillations in the static mode and load change mode is performed; ways for reducing and taking into account pressure fluctuations in the automatic control system of hydraulic turbine are identified in the paper.